The Impact of Performance Budgeting on Public Spending in Germany$1 (Bs Laenders - Lorenz, Christiane; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
After several years of practice, the question arises whether performance budgeting as one part of the New Public Management reforms has been effective. Derived from the international literature on experiences with performance budgeting Christiane Lorenz identifies five elements which constitute performance budgeting as a comprehensive system. This new definition is then applied to the German states in order to investigate whether performance budgeting actually leads to a reduction of public expenditure. With a survey in the state Ministries of Finance the impact of the German performance budgeting reforms on their major aim, the enhancement of fiscal discipline, is empirically analyzed. The main result is that the potential of expenditure savings is prolonged by the enormous investments in the beginning.
Keywords: Economics; Economics/Management Science; Economics/Management Science, general